Information technology and communication and best practices in it lifecycle management - Paletta,Francisco Carlos (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2008)
In this work, we focus on the role of Information and Communication Technologies - ICT- to create additional sources of competitive advantage that can help companies to prepare themselves for sustainable growth in the long term. First, we discuss the dynamics of ICTs and the ability to generate innovations with a direct impact on business.Then we present the need for greater balance between goals of short and long term on IT projects. In the third part, we discuss how these new technologies have helped to increase the productivity of information professionals as well as to enhance decision-making process and the satisfaction of the end customer. To conclude, it is presented the main challenges that the technology-based companies will have to face in relation to the management of the lifecycle of their technology, consolidation and simplification of their processes within their computing environments, aiming to increase productivity and develop agile environments that allow the organizations to meet the demands of managing digital information.